Nanoparticles Technology - Aliofkhazraei, Mahmood (IntechOpen, 2015)
During the past years, scientists have achieved significant success in the nanoscience and nanotechnology. Nanotechnology is a field of applied sciences which is focused on design, production, detection, and employing the nano-size materials, pieces, and equipment. Advances in nanotechnology lead to improvement of tools and equipment as well as their application in everyday life. In the chemistry this size involves the range of colloids, micelles, polymer molecules, and structures such as very large molecules or dense accumulation of the molecules. In physics of electrical engineering, the nanoscience is strongly related to quantum behaviour or electrons behaviour in structures with nano sizes. Also, in biology and biochemistry, there are interesting cellular components and molecular structures. This book collects new developments about nanoparticles.